33.1 Meänkieli Ruottissa: Raportin yhtheenveto ELDIA-projektissa - Arola, Laura
Meänkieli (Tornedal Finnish) translation of the abridged version of the report on the case study on the Meänkieli language in Sweden, conducted within the EU-FP7 research project ELDIA